Plant-based repellents and insecticides for cockroach control: A comprehensive review - Malik, Adeena; Mehmood, Khalid; Nadeem, Muhammad Sajid; Malik, Khafsa (Journal of Pure and Applied Agriculture, 2023)
Cockroaches associated with human habitat, act as vectors and produce allergens. Synthetic insecticides are commonly used to control cockroaches, but they have a negative impact on human health and the environment. Moreover, cockroaches develop resistance to insecticides. On the other hand, plant-based insecticides are more eco-friendly and safer than chemical- based. The development of resistance in pests to plant-based insecticide products is slower due to the presence of various chemical compounds. In this review article, data has been compiled regarding the use of plant constituents (phytochemicals, essential oils) that control cockroaches, and can be used as an alternative to synthetic chemicals. They act in different ways namely repellent, insecticidal, and antifeedant. This review focuses on the efficacy of plant-based materials against two species of cockroaches (Periplaneta americana L., and Blattella germanica L.). Different methods were enlisted here which were used to assess the plants to control cockroaches. This article will be helpful for researchers to select suitable plant species, plant parts and methods to control cockroaches as well as other related species of insects. The phytochemicals present in plants should be isolated and can be used for manufacturing biopesticides.